Performance evaluation of multibed adsorbent on removal of hexavalent chromium through various kinetic models - Lalitha, L. M.; Mariraj Mohan, S. (Journal of Environmental Engineering and Landscape Management, 2018)
In this study, an idea of using multiple layers of adsorbents in adsorption column is proposed for treatment of synthetic wastewater for removal of Cr(VI) ions. In the present study, an effort has been made to study and compare the performance of fixed bed column with single bed adsorbent (RH only) and multi bed adsorbent of Rice Husk (RH), Saw Dust (SD) and Coir Dust (CD) in removal of Cr(VI) from synthetic wastewater and arrive at the parameters of the adsorption column that are useful for process design. From the characterization studies, it has been observed that carbon, aluminium and silica were the major components of the three natural adsorbents studied. It was found that, for better heavy metal removal, natural adsorbents with a percentage of fineness of around 54% could be used in adsorption studies. From the breakthrough curves of single bed and multi bed adsorption columns, it was evident that the multi bed adsorption column performed better. The time taken to achieve the breakthrough point and the exhaustion point in multi bed column is 2.5 times and 1.9 times greater than the time taken by single bed adsorption studies respectively. It was observed that in multi bed adsorption column, at greater bed depths, the significant increase in metal uptake capacity was due to the increase in contact time. Kinetic models viz. Thomas model, Yoon-Nelson model and Bed Depth Service Time model (BDST) were used to predict the performance of the column and sum of squares (SS) error analysis was carried out to test the accuracy of model equations. Higher R2 value and smaller SS value obtained from Thomas model proves that it is suitable to explain the adsorption of Cr(VI) in single and multi bed adsorption column of natural adsorbents. Experimental data fitted well with BDST model where R2 = 0.997. From the cost analysis, multi bed adsorption column was proven to be economical and confirmed that the locally and abundantly available agricultural wastes viz. RH, SD and CD could be used as an alternate to commercially available activated carbon for the removal of Cr(VI) from synthetic wastewater.